A Catalyst‐Free Cycloaddition Reaction: Access to Spiro[chroman‐3, 2'‐indene‐1', 3'‐dione] Scaffolds. Issue 35 (11th December 2017) - Han, Yuzhe; Zhu, Yingzu; Zhang, Pangmiaomiao; Li, Wenjun; Li, Pengfei
Abstract: We have reported herein a catalyst‐free cycloaddition of ortho ‐hydroxyphenyl‐substituted para ‐quinone methides and 2‐arylideneindane‐1, 3‐diones by which a series of chromans featuring a spiro indane‐1, 3‐dione scaffolds were obtained in high yields without any additives. Importantly, both anti ‐ and syn ‐ diastereomers could be obtained as single diastereomers respectively. Moverover, the current methold provides a novel and convenient approach for the efficient incorporation of the two biologically important scaffolds (chroman and spiro indane‐1, 3‐dione). Abstract : A catalyst‐free cycloaddition of ortho ‐hydroxyphenyl‐substituted para‐quinone methides and 2‐arylideneindane‐1, 3‐diones has been developed for the construction of spiro[chroman‐3, 2'‐indene‐1', 3'‐dione] scaffolds. Notably, both anti‐ and syn ‐diastereomers could be obtained as single diastereomer via this methodology.